Strengthening the Structure and Competitiveness of Financial Performance, Digital Technology, for the Sustainability of BPR/S Profitability, Will It Be Successful? - Sinaga, Imelda; Yohannes Suharsana (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is: to obtain the urgency of analysis on the influence of GCG, DTI, GCG*DTI, NPL, CR, CAR and EAQ on ROA. The method used is multiple linear regression with secondary data on purposive random sampling collection using annual financial reports and BPR/S GCG reports in 2024. The results of the study show that there are insignificant findings on GCG, DTI, GCG*DTI, NPL, CR, CAR and EAQ on BPR/S ROA. This shows that strengthening the structure and competitiveness of financial performance, digital technology, for the sustainability of the profitability of people's/Islamic economic banks still needs to be improved and managed further because the situation of BPR/S is experiencing problems, especially in small banks that have low liquidity, poor risk management, technology that has not been adopted well, an increase in non-performing loans and the economic conditions of the community that are under pressure and affect customer payment power. The implications of this research are that the Financial Services Authority (OJK) and Bank Indonesia can strengthen oversight and implementation of established regulations and protect customer interests through a roadmap for the development and strengthening of the rural bank (BPR/S) industry for 2024-2027, incorporating leadership and change management, the quantity and quality of human resources, digital technology infrastructure, and sectoral collaboration and cooperation. This will enable BPR/S management to address fundamental issues related to capitalizing on opportunities and managing risks through the expansion of BPR/S business and activities.